Mitochondrial Quality Control Strategies: Potential Therapeutic Targets for Neurodegenerative Diseases? - Hu, Di; Liu, Zunren; Qi, Xin (Frontiers in Neuroscience, 2021)
Many lines of evidence implicate the therapeutic potential of rescuing mitochondrial integrity by targeting specific mitochondrial quality control strategies in neurodegenerative diseases such as Parkinson's disease, Huntington's disease, and Alzheimer's disease. In addition to ATP synthesis, the mitochondrion is a critical regulator of ROS production, lipid anabolism, calcium buffering, and cell death. Mitochondrial unfolded protein response, mitochondrial dynamics and mitophagy are the three main quality control strategies responsible for maintaining mitochondrial proteostasis and bioenergetics. The proper function of these complex quality control strategies is necessary to surveil and restore mitochondrial homeostasis and the healthy pool of mitochondria in the cell. Mitochondrial dysfunction occurs early and acts causally in disease pathogenesis. A growing body of evidence suggests that the significant accumulation of mitochondrial damage resulting from compromised quality control pathways, which are impaired by an impressive number of disease-specific proteins, leads to the development of neuropathology. Moreover, genetic or pharmaceutical manipulations that target quality control strategies can sufficiently rescue mitochondrial integrity and ameliorate disease progression. Thus, therapies aiming to improve mitochondrial quality control strategies hold great promise for neurodegenerative diseases. In this review, we summarize recent progress that underscores the essential role of impaired mitochondrial quality control pathways in the pathogenesis of neurodegenerative diseases. We also discuss the translational approaches targeting mitochondrial function with a focus on the restoration of mitochondrial integrity, including mitochondrial dynamics, mitophagy, and mitochondrial proteostasis.